(untitled) (One Health & Risk Management, 2024)
Introduction. In recent years, the incidence of infectious diseases affecting the central nervous system has increased. Among the reasons for the expansion of these diseases and the emergence of new neuropathogens are globalization, global warming, increased proximity between humans and wild animals due to human activities such as deforestation, the rising cases of antimicrobial resistance, etc. Material and methods. A narrative synthesis of specialized bibliographic references was conducted, selecting sources from Google Scholar and ResearchGate using the keywords “bacterial diseases of the nervous system,” “neuroinfections,” and “global warming” in English. A total of 39 bibliographic sources were identified, excluding 3 abstracts and 4 duplicated articles. Additionally, 19 irrelevant articles were excluded, and 4 articles highlighting the topicality of the subject were added. Results. Bacterial diseases affecting the nervous system tend to become increasingly severe due to the critical functions performed by the brain, spinal cord, peripheral nerves, and cranial nerves. Infections can occur in nervous tissue or in the meninges (covering membranes). Specialized literature mentions that there is no direct connection between neuroinfections and global warming. The development of neuroinfections is linked to exposure to bacterial agents in the environment and is associated with human behaviors. Although global warming can influence the distribution of disease vectors, there is a significant distance between this phenomenon and the direct transmission of neuroinfections. Global warming can impact human health in various ways, including the expansion of the range of vector-borne diseases or changes in the distribution of pathogens. However, these connections are complex and depend on numerous factors. Conclusions. The effects of global warming can enhance the adverse impact of microorganisms on the nervous system.